Desarrollo de un modelo de diagnóstico para la recuperación de proyectos con desviaciones de alcance, tiempo y costo (2015)
In accordance with the purpose and objectives of this Degree Work, initially defined, after a documentary search, those metrics that can generally be used in modern project management, to measure the general state of a project and in turn raise objectives of quality for the assurance of the same. With this information, five metrics that are the basis for the development of the Diagnostic Model were defined, as follows: Project definition level, Project global risk level, Project performance index (Earned Value), Customer satisfaction level and Level of motivation of the work team of the project. Based on the defined metrics, checklists were prepared to carry out the survey of the information that allows to diagnose the "health status" of the project. These checklists in turn are the input for the creation of a parametric tool, designed by the Grade Work team in Microsoft Excel. The tool allows, in a simple and orderly manner, to collect the project information, and to obtain based on it a consolidation of the results of the diagnosis, which depend in all cases on the tolerance levels defined by the Organization that owns the project. analyzing. This tool is accompanied by a general application methodology, which is proposed to carry out the process of project diagnosis. Both the methodology and the tool that make up the diagnostic model, product of this Degree Work, were applied to three projects selected from two different sectors of the Colombian industry (energy sector and real estate sector). The application of the model is done in order to prove the applicability of it, and verify that it can be used indistinctly in any project, obtaining valid results, thanks to its main characteristic, which is the parameterization of all the variables. Based on the application of the tool developed and the analysis of the results obtained, some recommendations were proposed for the projects under test. Furthermore, it was concluded that the product obtained with this Degree Work will allow each Project Manager or Company that uses it to obtain information jointly on the strengths and critical points or flaws presented by the project, said information being useful for proposing actions of insurance or, if necessary, recovery plans. Additionally, for the successful development of the degree work, tools and elements of modern project management were applied, using as reference the "Fundamental Guide for project management" of the PMI in its fifth edition. Based on the above, a Management Plan was proposed for the project, the project activities were carried out, both in development and management, and monitoring and control was carried out through biweekly monitoring reports that were presented and analyzed in meetings of the project team with the director of the degree work. Finally, the project was closed, in addition to presenting a final project report, an exercise was carried out to identify and record the lessons learned.